Expeditious Routes to Polycyclic Molecular Frameworks via One-Pot, Two-Step Ugi Ring-Closing Sequences - Xu, Zhigang; De Moliner, Fabio; Cappelli, Alexandra P.; Ayaz, Muhammed; Hulme, Christopher (Synlett, 2014)
A very general and robust multicomponent-reaction protocol involving an Ugi condensation between ethyl glyoxylate, isonitriles, N-Boc-α-amino acids, and mono-N-Boc-protected diamines followed by a series of acid-promoted cyclization steps in a one-pot fashion is reported. This process allows for the assembly of complex polycyclic structures by means of just two simple synthetic operations and a single chromatographic purification in high overall yields. Of note, the first scaffolds derived from a highly selective sequence of ring-closing events involving three internal amino nucleophiles is reported.
Keywords: multicomponent reaction; nucleophilic attack; heterocycles; isonitriles; one-pot process